2023
DOI: 10.3389/fncel.2022.1037903
|View full text |Cite
|
Sign up to set email alerts
|

Brain-enriched miR-128: Reduced in exosomes from Parkinson’s patient plasma, improves synaptic integrity, and prevents 6-OHDA mediated neuronal apoptosis

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disorder associated with the death of mid-brain dopaminergic neurons. Unfortunately, no effective cure or diagnostic biomarkers for PD are available yet. To address this, the present study focuses on brain-enriched small non-coding regulatory RNAs called microRNAs (miRNAs) that are released into the circulation packaged inside small extracellular vesicles called exosomes. We collected blood samples from PD patients and isolated exosomes from the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…One study used both CNS‐originating EVs and general EVs for ROC analysis, and we did not exclude it (Yan et al., 2022). Among the studies using general EVs, thirty of those studies did not include an ROC analysis (Athauda et al., 2019; Bhattacharyya et al., 2022; Cerri et al., 2018; Chan et al., 2023; Chan et al., 2021; Chan et al., 2023; Chung et al., 2020; Elkouris et al., 2019; Fraser et al., 2016; Han et al., 2019; Herman et al., 2023; Ho et al., 2014; Hong et al., 2023; Kitamura et al., 2018; Lamontagne‐Proulx et al., 2019; Leng et al., 2020; Leng et al., 2022; Miyamoto et al., 2023; Sproviero et al., 2021; Sproviero et al., 2022; Taymans et al., 2023; Wang et al., 2017; Wang et al., 2018; Wang et al., 2020; Wang et al., 2022; Xia et al., 2019; Yang et al., 2015; Yang et al., 2018; Yeh et al., 2021; Zhao et al., 2020), six did not include sensitivity or specificity (Grossi et al., 2021; Gualerzi et al., 2019; He et al., 2021; Ohmichi et al., 2019; Ruf et al., 2021; Yao et al., 2018), and one study only performed the ROC analysis directly in serum instead of EVs (Citterio et al., 2023). In total, the meta‐analysis included 21 studies (Barbagallo et al., 2020; Cao et al., 2019; Cao et al., 2020; Cao et al., 2017; Chung et al., 2021a; Chung et al., 2021b; Dos Santos et al., 2018; Gui et al., 2015; Hadisurya et al., 2023; Hong et al., 2021; Lucien et al., 2022; Manna et al., 2021; Shim et al., 2021; Stuendl et al., 2016; Stuendl et al.,…”
Section: Resultsmentioning
confidence: 99%
“…One study used both CNS‐originating EVs and general EVs for ROC analysis, and we did not exclude it (Yan et al., 2022). Among the studies using general EVs, thirty of those studies did not include an ROC analysis (Athauda et al., 2019; Bhattacharyya et al., 2022; Cerri et al., 2018; Chan et al., 2023; Chan et al., 2021; Chan et al., 2023; Chung et al., 2020; Elkouris et al., 2019; Fraser et al., 2016; Han et al., 2019; Herman et al., 2023; Ho et al., 2014; Hong et al., 2023; Kitamura et al., 2018; Lamontagne‐Proulx et al., 2019; Leng et al., 2020; Leng et al., 2022; Miyamoto et al., 2023; Sproviero et al., 2021; Sproviero et al., 2022; Taymans et al., 2023; Wang et al., 2017; Wang et al., 2018; Wang et al., 2020; Wang et al., 2022; Xia et al., 2019; Yang et al., 2015; Yang et al., 2018; Yeh et al., 2021; Zhao et al., 2020), six did not include sensitivity or specificity (Grossi et al., 2021; Gualerzi et al., 2019; He et al., 2021; Ohmichi et al., 2019; Ruf et al., 2021; Yao et al., 2018), and one study only performed the ROC analysis directly in serum instead of EVs (Citterio et al., 2023). In total, the meta‐analysis included 21 studies (Barbagallo et al., 2020; Cao et al., 2019; Cao et al., 2020; Cao et al., 2017; Chung et al., 2021a; Chung et al., 2021b; Dos Santos et al., 2018; Gui et al., 2015; Hadisurya et al., 2023; Hong et al., 2021; Lucien et al., 2022; Manna et al., 2021; Shim et al., 2021; Stuendl et al., 2016; Stuendl et al.,…”
Section: Resultsmentioning
confidence: 99%
“…Their functional mechanisms include the replacement of dopaminergic neurons, immune regulation, inhibition of apoptosis and inflammation, and neuroprotection ( Chen et al, 2020 ; Heris et al, 2022 ). MSCs have remarkable potential in the treatment of PD, as they not only differentiate into dopaminergic neurons but also secrete a wide range of molecules, including exosomes containing miRNAs ( Staff et al, 2019 ), which participate in intercellular signaling and crosstalk with host glial cells ( Liu et al, 2022 ; Bhattacharyya et al, 2023 ). The MSC secretome plays a crucial role in regulating axonal growth and suppressing cell apoptosis.…”
Section: Stem Cell Transplantation For Pdmentioning
confidence: 99%
“…MiRNAs are another kind of biomolecule usually present in exosomes. Pallab Bhattacharyya et al reported that miR-128 was down-regulated in plasma-derived exo somes from PD patients [106]. Yao et al reported that the level of miR-331-5p from PD patients' plasma exosomes was increased, while that of miR-505 was decreased [107] Cao et al found that the level of miR-24 and miR-195 in PD patients' exosomes were ele vated, while that of miR-19b was reduced [108].…”
Section: Exosomes-based Diagnosis Of Pdmentioning
confidence: 99%